MOTIVASI DAN PERSEPSI WISATAWAN NUSANTARA BERKUNJUNG KE JATILUWIH, TABANAN - Ayu Diah Utari, Ni Made; Wijaya, NMS.; Sudana, I Putu (Jurnal IPTA (Industri Perjalanan Wisata), 2021)
This research is done by four national tourist motivations namely physical motivation, culture motivation, social motivation, and fantasy motivation. Perception of domestic tourists is assessed from the tourism component, namely attraction, accesibility, amenities, ancilary services. This research has a purpose 1) to determine the motivation of Indonesian tourists visiting Jatiluwih tourist attraction, Tabanan regency. 2) to find out the perception of Indonesian tourists about the main components in tourism (4A) in the tourist attraction of Jatiluwih, Tabanan regency. This research uses purposive sampling method with the method of taking informants is accidental sampling and distributing questionnaires to 125 respondents of domestic tourists. The data collection tehniques used were observatio, interview, questionnaires, literature study, documentary study and the data analysis tehniques were descriptive qualitative and quantitative descriptive. The results of this study indicate that the highest motivation for domestic tourists to visit Jatiluwih tourist attraction is to enjoy the natural atmosphere and terraced rice fields,  Jatiluwih ia a World Cultural Heritage, to interact with local people or farmers in Jatiluwih, and to seek new experiences. The perception of tourists towards the main components in tourism in the overall research is good. However, tourists feel that they are lacking in ancilary service on the indicator of the availability of ATM because these facilities are inadequate.